2006
DOI: 10.21273/hortsci.41.1.108
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity of Volatile Alcohols on the Germination and Growth of Radish Seedlings

Abstract: A series of experiments were conducted to determine the sensitivity of radish to four light alcohols (ethanol, methanol, 2-propanol, and t-butanol) identified as atmospheric contaminants on manned spacecraft. Radish (Raphanus sativus L. `Cherry Bomb' Hybrid II) seedlings were exposed for 5 days to concentrations of 0, 50, 100, 175, 250, and 500 ppm of each alcohol and the effect on seedling growth was used to establish preliminary threshold response values. Results show a gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…CO 2 is delivered to the individual chambers via the facility's CO 2 supply, which has been passed through silica, activated carbon, and Purafilä (Purafil, Doraville, GA) filters before being mixed with filtered breathing air. This design provides removal of ethylene and volatile organic compounds that affect plant growth (Eraso et al, 2003;Stutte, 1999;Stutte et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…CO 2 is delivered to the individual chambers via the facility's CO 2 supply, which has been passed through silica, activated carbon, and Purafilä (Purafil, Doraville, GA) filters before being mixed with filtered breathing air. This design provides removal of ethylene and volatile organic compounds that affect plant growth (Eraso et al, 2003;Stutte, 1999;Stutte et al, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…It is not yet known which component(s) of the wastewater are likely to be responsible for the chronic phytotoxicity observed, however there is some evidence suggesting that sodium [28], ethanol [29] and polyphenols [10] are all potentially phytotoxic constituents. The detailed analysis of inorganic components in the root and shoot tissue, presented here, provide some insights.…”
Section: Effects Of Winery Wastewater Application On Plant Growth Andmentioning
confidence: 99%
“…There is a lack of information on the contribution of organic acids and tannins toward toxicity. Ethanol phytotoxicity has been reported by some studies [21,22]. Murin [21] indicated a low value of LC 50 of ethanol for Vicia sativa, 3 mL L −1 .…”
Section: Garden Cress Testmentioning
confidence: 99%
“…Murin [21] indicated a low value of LC 50 of ethanol for Vicia sativa, 3 mL L −1 . Stutte et al [22] tested ethanol toxicity to radish seedlings and suggested that damage could be due to membrane disruption associated with phospholipid extraction from the cell. Our results and previous literature indicates that WW is a complex toxic mixture.…”
Section: Garden Cress Testmentioning
confidence: 99%